Pengembangan Usaha Pembenihan Ikan Nila di Kabupaten Konawe - Muhammad Mujur; Ayub M. Padangaran; Muhammad Arief Dirgantoro (Jurnal Sosio Agribisnis, 2020)
This study aims to analyze the factors that influence the production of tilapia hatchery business, and to analyze the development of tilapia hatchery business in Konawe Regency. The population in this study were all members of the Tilapia hatchery business group. Sampling was done by simple random sampling by taking a sample of 50 cultivators. The data collected consists of: the value of the equipment used, the number of broodstock, the amount of feed, the area of the pond, the number of workers, the amount of fish seed production, the price of input or production factors, and the price of production (fish seeds). Data were analyzed using descriptive statistics and inferential statistics. The results of the study showed that the production factors of tilapia hatchery business in Konawe Regency which consisted of equipment value, number of broodstock, amount of feed, pond area, and number of workers had a significant effect on production. Tilapia hatchery business is in a condition of Increasing Return to Scale. Thus, the use of production factors is not efficient so that it needs to be developed.Key words: business development; hatchery; parrot fish